Sobre a provável parafilia de Centrotinae Amyot & Serville (Homoptera, Membracidae) - Creão-Duarte,Antônio José (1992)
An alternative proposition for the analysis of the diagnostic states of the pronotum in the Centrotinae and Membracinae (sensu Strümpel) is presented. In this analysis, a linear transformation series is proposed for this character, departing from the state found in Tolania Stal, 1858 changing to an intermediate state in Centrotinae, which is still treated as plesiomorphic when compared with the one found in Membracinae. The transformation series thus defined, clarifies the problems related to the monophyly of the Membracidae, which is herein supported by the state of pronotum previously used to define the Centrotinae. This later taxon is treated as paraphyletic. The monophyly of the Membracinae is unquestioned, but its sister group is still unknown. Finally, this analysis permitted the reinterpretation of several characters, previously treated as homoplasies, now as synapomorphies.